Properties of ZnO nanorods grown by hydrothermal synthesis on conductive layers. Issue 8 (9th July 2014) - Podrezova, L.V.; Cauda, V.; Stassi, S.; Cicero, G.; Abdullin, Kh. A.; Alpysbaeva, B. E.
<x xml:space="preserve">Abstract</x> Zinc oxide nanorods were hydrothermally grown from water solution on different conductive substrates. In particular, several metal layers, such as Cu, Ni, Pt, Ag, Au, deposited on silicon substrates, and F‐doped SnO2 coated‐glass wafers were investigated as bottom electrodes and their influence on the properties of the synthesized nanorods were studied. The samples were characterized by scanning electron microscopy, X‐ray diffraction, atomic force microscopy, current ‐ voltage and photoluminescence measurements. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>